Superimposed Rifting at the Junction of the Central and Equatorial Atlantic: Formation of the Passive Margin of the Guiana Shield. Issue 7 (13th July 2021) - Loparev, Artiom; Rouby, Delphine; Chardon, Dominique; Dall'Asta, Massimo; Sapin, François; Bajolet, Flora; Ye, Jing; Paquet, Fabien
Abstract: The passive margin of the Guiana Shield formed at the junction of the Central and Equatorial Atlantic Oceans that developed successively by a complex rifting process that achieved the final dispersal of Western Gondwana. Yet, the resulting spatial distribution of crustal thinning along the margin remains to be mapped and its controlling parameters deciphered. We used subsurface data to map the variability of crustal thinning along the margin. We show that the margin segments width primarily depends on their obliquity to rifting extension direction. The necking domain of the transform/oblique margin segments is much narrower (<100 km) than divergent segments that include hyper‐extended or distal margin domains as well (200–300 km). Moreover, for a similar obliquity, the width of margin segments resulting from the Central Atlantic rifting are wider than those resulting from the Equatorial Atlantic rifting. This is primarily due to the higher obliquity and rate of the latter. Additionally, along the Central Atlantic margin segments, thinning was accommodated by lower‐crustal ductile deformation, the thick syn‐rift in‐fill was associated with magmatism and a thicker than average oceanic crust. In contrast, the Equatorial Atlantic margin segments show little ductile deformation, reduced clastic syn‐rift infill and thinner than average oceanic crust. These observations suggest that the lithosphere affected by the Central Atlantic rifting was warmer than that affected by the Equatorial Atlantic rifting. Finally, the two‐step thinning in the overlapping area of the two rift systems individualized a promontory of thinned continental crust that remained as the Demerara Plateau. Plain Language Summary: The continental margin of the Guiana Shield formed at the intersection of the Central and Equatorial Atlantic Oceans that developed one after the other and, in doing so, achieved the break‐up of the Gondwana supercontinent. To form these Ocean, the continent crust was stretched and broke but the way this thinning is actually varying along the margin and the causes are not known so we used offshore industrial data to map it. This allows us showing that the width of the continental margin depends primarily on the direction along which the crust was thinned such that the continental margin width is much wider (200–300 km) in domains where this direction is perpendicular to the margin than in domain where it is oblique (<100 km). This also allow us showing that the continental margin resulting from the opening of the Central Atlantic Ocean is systematically wider than the one resulting from the opening of the Equatorial Atlantic. Additionally, our observations suggest that Central Atlantic Ocean opened under warmer conditions than the Equatorial Atlantic. Finally, the area at the intersection of the Central and Equatorial Atlantic Oceans, individualized a promontory of continental crust that formed the present‐day Demerara Plateau. Key Points: Higher rifting obliquity and rates produced narrower rift and rifted margin segments Warmer Central Atlantic rifting produced crustal flow and preserved thick syn‐rift deposits contrary to cooler Equatorial Atlantic rifting Lithosphere of the Demerara Plateau was thinned twice and became a buoyant continental raft since the Mid‐Cretaceous